Monitoring of the spread and development of pests and diseases in sugar beet stands - Sabluk, V.; Zapolska, N.; Shendryk, K.; Dymytrov, V. (Quarantine and plant protection, 2022)
Goal. To determine the spread and development of pests and diseases in sugar beet crops and their threat to crop plants. Methods. Analysis of the reports of regional forecasting and signaling laboratories of the State Vetphytosanitary Service of Ukraine and the results of own observations conducted at research and breeding stations of the Institute of Bioenergy Crops and Sugar Beet of the National Academy of Sciences of Ukraine and beet farms of Ukraine regarding the prevalence and development of phytophages and pathogens, their reservation in agrocenoses. Determination of the threat from them to crops according to the Methodology of research in entomology and phytopathology and the Methodology of conducting research in beet growing. Results. It was established that certain types of pests have a significant reservation in agrocenoses and other stations and annually threaten sugar beet crops in various beet harvesting zones. In particular, from year to year, the greatest danger to crop seedlings and plants during their growing season is caused by beetles of the common beet weevil Asproparthenis punctiventris (Bothynoderes punctiventris Germ.), the number of which significantly exceeds the economic threshold of its harmfulness. Among other types of harmful insects that annually threaten sugar beet crops, the gray beet weevil (Tanymecus palliates F.), beet fleas (Chaetocnema sp.), shieldworms (Cassida sp.), stem weevil (Lixus sultilis Beh.) will be dangerous in future years.), the number of which varies within the thresholds of their harmfulness. Regarding diseases, there is still a threat of significant damage to culture plants by cercospora (Cercospora beticila Sacc.), fomosis (Phoma betae Frank), powdery mildew (Erysiphe communis (Wallr Grev f.betae Jacz.)), and others. In particular, according to observations, cercosporosis is gaining pace of intensive development due to favorable weather conditions, so we recommend farms to take measures to reduce plant damage. Precipitation, which passes through centers at the end of summer in most regions of Ukraine, can lead to significant susceptibility of root crops to various types of rot, which can also lead to a decrease in crop yield and quality deterioration. Conclusions. In recent years, favorable conditions have been created in Ukraine for the development and spread of many types of pests and diseases in sugar beet crops, which leads to an increase in their harmfulness compared to previous seasons. In particular, the population density of beetles of the common beet weevil was 2—18 specimens/m2, which is ten times higher than the standard. The same applies to other pests and diseases, a significant reserve of which may threaten crops in the coming year.